Problem Diskriminasi Peserta Didik Penganut Kepercayaan di Kota Malang - Yohanes Victor Baro Bitan; Firgianus Botu; Bonifacius Gendis Permiro (Equilibrium: Jurnal Pendidikan, 2024)
Freedom of religion is the right of every human being. In Indonesia, freedom of religion has been guaranteed by the government in law. But often in practice there are still many violations in the name of religion. This research study pays attention to the discrimination against students of believers in every education unit in Malang City. Of course, this contradicts the fifth principle in which everyone has the same rights. One of those rights is the right to get a proper education. This research uses a qualitative approach, namely the literature study method and by relying on some previous research data to examine discrimination cases that are currently rampant in Malang City. The theoretical framework used as an analytical knife is Emmanuel Levinas' perspective on responsibility and attention to others if it becomes a light in analyzing cases of discrimination. The results of the study reveal that discrimination occurs because of the mentality of a society that does not accept differences. So the solution offered is character building and improvements to the education system that must prioritize the quality of education, not the background of students.